THE EFFECT OF STAD-TYPE COOPERATIVE LEARNING MODEL (STUDENTS TEAMMS ACHIEVEMENT DIVISION) ON ONE-VARIABLE LINEAR EQUATION MATERIAL ON LEARNING OUTCOMES VIEWED FROM THE SELF EFFICACY OF SMP N 2 GODEAN - Nanang Khuzaini; Hilliyani Hilliyani (Renjana Pendidikan Dasar, 2023)
The background of this research is based on the researcher's interviews with teachers in the field of mathematics who teach at SMP N 2 Godean, it is known that students' understanding of mathematics is still low, it is known from the scores of assignments and students' daily tests that are still below the KKM, namely 75. Even though learning outcomes are often used as a benchmark for achieving educational goals. In order for student learning outcomes to be better, the teacher requires students to be more confident in working on math problems, such as working on one-variable linear equation problems, students are expected to foster the self-efficacy of each individual. One alternative learning model that supports self-confidence is using STAD type cooperative learning model. This study aims 1) to determine the type of STAD cooperative learning model affects learning outcomes. 2) to determine self-efficacy influences learning outcomes. 3) to determine the interaction between the STAD cooperative learning model and self-efficacy on learning outcomes. This study used a quantitative approach. The subjects of this study were class VII students of SMP N 2 Godean, taking samples using a purposive sampling technique. This research included the type of pretest-posttest group design experimental research. The instruments used were learning achievement tests and self-questionnaires. efficacy. The data analysis technique used is the Two Way ANOVA test. The results showed that 1) there was an influence of the STAD type cooperative learning model on learning outcomes with Fcount 5.428 > Ftable 3.991. 2) there is an effect of self-efficacy on learning outcomes with Fcount 40.804 > F table 3.140. 3) there is an interaction between the STAD cooperative learning model and self-efficacy on learning outcomes Fcount 4,387 > from Ftable 3,140 The conclusions in this study are 1) There is an influence of the STAD type cooperative learning model on learning outcomes. 2) There is an effect of self-efficacy on learning outcomes. 3) There is an interaction between the STAD cooperative learning model and self-efficacy on learning outcomes. It is recommended that teachers use the STAD type cooperative learning model which can be used as an alternative learning model for teachers to improve student learning outcomes